Given,

\(\displaystyle{9}{p}^{{{2}}}-{24}{p}+{16}\)

Step 2

On simplification, we get

\(\displaystyle{9}{p}^{{{2}}}-{24}{p}+{16}={9}{p}^{{{2}}}-{12}{p}-{12}{p}+{16}\)

=3p(3p-4)-4(3p-4)

=(3p-4)(3p-4)

\(\displaystyle={\left({3}{p}-{4}\right)}^{{{2}}}\)

\(\displaystyle{9}{p}^{{{2}}}-{24}{p}+{16}\)

Step 2

On simplification, we get

\(\displaystyle{9}{p}^{{{2}}}-{24}{p}+{16}={9}{p}^{{{2}}}-{12}{p}-{12}{p}+{16}\)

=3p(3p-4)-4(3p-4)

=(3p-4)(3p-4)

\(\displaystyle={\left({3}{p}-{4}\right)}^{{{2}}}\)